Selecting environmental indicators for the evaluation of coastal risks in the Galicia-North Portugal Euroregion - Bastero, S. F.; Castro, Carmen G. (2018)
1 poster.-- VI International Symposium on Marine Sciences, Vigo (Spain), 20-22th June 2018.-- S. F. Bastero . et al. Coastal regions are among the most productive and valued ecosystems in relation to their ecosystem services (Millenium Ecosystem Assessment 2005; Hattam et al., 2015). However, their degradation is dramatically growing due to the increase of human pressure on coastlines that can negatively impact or threaten marine habitats. The evaluation of potential marine risks (Crain et al, 2009) emerges in response to the growing concern of the society about increase of frequency and intensity of natural disasters and environmental problems associated with the socio-economic development, such as pollution, resources depletion and climate change. In this context, the MarRISK project (0262_MARRISK_1_E) focuses on the consolidation of a knowledge infrastructure for evaluating coastal risks in the Galicia-North Portugal Euroregion. This EU project joins experts in Marine Sciences from MeteoGalicia, APA, CETMAR, CIIMAR, IEO, IH, IIMCSIC, INTECMAR, IPMA, LMAG, UAveiro, UMinho and UVigo. This multidisciplinary partnership constitutes an optimum platform to achieve the proposed objective. The MarRISK team has identified forty-two environmental indicators (EEA, 2014) of coastal risks that threaten the ecosystem services of the Galicia-North Portugal Euroregion. In the Galician region, emerging identified risks (eutrophication, hydrodynamic alteration, oceanic warming, algal blooms regime changes and ocean acidification) directly affect supporting and provisioning services. In contrast, for the Northern Portuguese region, coastal erosion and flooding have been identified as the most pressing risks, impacting regulating and cultural services. As a first step to assess coastal risks, environmental indicators have been established, integrating information from different environmental concerns. The proposed environmental indicator list represents a useful tool not only to evaluate environmental trends, but also to ...